Effect of Modified Atmospheric Packaging (MAP) treatment on post-harvest quality of different varieties of kiwifruit (Actinidia spp.) under Cool bot storage condition - Dhakal, Mira; Gautam, Ishwori Prasad; Pandey, Suprabha; Poudel, Sujata; Ghimire, Dipendra (Nepalese Horticulture, 2022)
Kiwifruit is one of the leading agricultural commodities having the tremendous potential of export to the international market. An experiment was carried out during the period of 20th January to 20th June, 2020 to evaluate the efficacy of modified atmosphere packaging (MAP) on quality and physiochemical characteristics in cool bot storage conditions. There were altogether four varieties and twenty-five fruits of each variety were sealed with modified atmosphere packaging films of 25µ with standard 16 perforations stored in cool bot storage (6-7°Cwith 95-97% RH) condition. The Physiological weight loss %, Cumulative Weight loss (%), Total Soluble Solids(°Brix), Titrable Acidity (%), Vitamin C content, Color changes were obtained according to the measurements applied at harvest and during the storage periods. Though the treatment showed a non-significant effect, the maximum physiological weight loss was observed in Abbott (13.6%) and the minimum was in Hayward (9.21%) at 140 days of cool bot storage whereas cumulative weight loss (%) was the maximum in Allison (71.49%) and the minimum in Hayward (41.29%). The Total Soluble solid(TSS°Brix) were increased and Titrable Acidity (%) and vitamin C content (mg/100 gm) were decreased with the advancement of the storage period. The color value (L*, a* and b*) were also analyzed, and the result showed that Modified Atmospheric Packaging has a beneficial effect to retard the ripening process of kiwifruit in cool bot storage. Thus, the research revealed that modified atmosphere packaging (MAP) i.e. 25µ LDPE in a combination of cool bot storage was more effective to extend the marketable shelf life of kiwifruit without much affecting on quality perspectives.